Pengaruh Motivasi, Penghargaan Finansial, Pelatihan Profesional, Pertimbangan Pasar Kerja, Lingkungan Pada Karir Akuntan Publik - Rahayu, Putu Nanda; Asmara Putra, Nyoman Wijana (E-Jurnal Akuntansi; Vol 28 No 2 (2019), 2019)
The purpose of this study was to obtain empirical evidence of the influence of career motivation, economic motivation, financial rewards, professional training, consideration of the job market, the environment of friends and family in choosing a career as a public accountant. Methods Determination of samples in this study using purposive sampling technique. The sample of this study were regular accounting students at FEB Udayana class of 2015, amounting to 142 people. Data collection methods used with the questionnaire method in the form of a questionnaire. The data analysis technique used is the classic assumption test and multiple linear regression analysis. Based on the results of the analysis it was found that motivation which included career and economic motivation, financial rewards, professional training, consideration of the job market, friend and family environment had a positive effect on career choice as a public accountant. Keywords: Career motivation, financial rewards, professional training, consideration of the labor market, environment, and selection of a career in public accounting.